Fleuves, forêts et territoire dans les sources narratives des VIe et VIIe siècles - Guizard-Duchamp, Fabrice (Revue du Nord, 2003)
Abstract: „Through the major narrative sources available for the Gaul area of the vith and viith centuries (Grégoire de Tours, Frédégaire and his followers), the purpose of this paper is first to show in which way rivers and forests contribute to the geographical location of the events reported. The rivers appear essentially as obvious landmarks. Streams and rivers are real obstacles for the progression of armies in campaign. For princes who seek to master the territories of their regnum, the places where land routes cross rivers have a truly strategic importance. However, the rivers are not really considered as territorial limits.“
Keywords: Fluss; Gallien; Territorium; Wald